ANALISIS HUKUM TERHADAP KEWAJIBAN SERTIFIKASI ISPO (INDONESIAN SUSTAINABLE PALM OIL) DALAM KAITANNYA DENGAN PERTUMBUHAN INVESTASI DI INDONESIA (STUDI PADA PT REA KALTIM PLANTATION – JAKARTA) - Mutiara Panjaitan; Alvi Syahrin; Suhaidi Suhaidi; Mahmul Siregar (USU LAW JOURNAL, 2014)
ABSTRACT Both Indonesian Sustainable Palm Oil (ISPO) and the Roundtable on Sustainable Palm Oil (RSPO) are equally defined as a palm oil certification system that adheres to the principles of sustainable and environmentally growth for all plantation company. RSPO certification is a voluntary that differs from the ISPO which is compulsory (mandatory). ISPO obligations arises from the enactment of the Minister of Agriculture No. 19/Permentan/OT.140/3/2011 Guidelines on Sustainable Palm Oil Indonesia. For PT Rea Kaltim Plantation, as an RSPO certified and has obtained another sustainable and environmental certification, the obligation to implement ISPO regulation become the polemic since such regulation will obligated PT Rea Kaltim Plantation neither from the financial nor for the government aspect. Eventually, the status of the ISPO should be analyzed, since there is an argument that ISPO has no legal binding/legal force, meanwhile, according to the Agriculture Ministry which stated that the ISPO regulation is binding and has legal force, therefore, every Indonesian palm oil companies should become  the subject to such requirement.  ISPO legislation is binding by law because under the Article 8, paragraph (2) of Law No. 12 2011, states that the rules can be established by such authority. ISPO requirement is established by the duties and authority of the Ministry of Agriculture and therefore this requirement has any legal binding/legal force that set up for it. The higher legislation, equal to the Presidential Decree should be released in ordered to established ISPO requirement; the failure of the Government in promoting ISPO certification must be addressed; In addition of oversight the regulation of ISPO, the Indonesian oil palm companies should remained firm and commit in applying ISPO certification and. Keywords      : Roundtable on Sustainable Palm Oil (RSPO), Indonesian Sustainable Palm Oil (ISPO) Regulation, and Legal Position ISPO Regulation